ANALISIS PERANAN KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUASAN LAYANAN PADA DINAS PENCEGAH DAN PEMADAM KEBAKARAN KOTA MEDAN - TETI RAHMIATI HARAHAP (JURNAL ILMIAH KOHESI, 2021)
The concept of service quality related to satisfaction is determined by five elements commonly known as service quality"RATER" (responsiveness, assurance, tangible, empathy and reliability). The concept of rater service quality is essentially toform the attitudes and behaviors of service developers to provide a strong and basic form of service, in order to get anassessment in accordance with the quality of service received. The essence of the concept of service quality is to show allforms of actualization of service activities that satisfy people who receive services in accordance with responsiveness, fosterthe existence of assurance, show physical evidence (tangible) that can be seen, according to empathy (empathy) frompeople who provide services in accordance with their reliability (reliability) carrying out service tasks provided consequentlyto satisfy those who receive services. Based on the core of the concept of service quality "RATER" most work organizationsthat make this concept as a reference in applying the actualization of services in their work organizations, in solving variousforms of gaps (gaps) over various services provided by employees in meeting the demands of community services.Actualization of the concept of "RATER" is also applied in the application of the quality of service of employees bothgovernment and non-government employees in improving their work performance.